TERAPI INTERVENSI PADA NYERI KEPALA TIPE KLASTER - Hanik Badriyah Hidayati,* Santoso,** Isti Suharjanti,* Mohammad Hasan Machfoed* (NEURONA, 2017)
HEADACHE PREVIOUSLY KNOWN AS VARIAN OF MIGRENE IS NEUROVASCULAR HEADACHE CHARACTERIZED BY UNILATERAL HEADACHE AND ASSOCIATED WITH IPSILATERAL CRANIAL OTONOMIC SIGNS DIAGNOSIS OF CLUSTER HEADACHE IS MADE FROM HISTORY TAKING AND PHYSICAL EXAMINATION THE MAIN MANAGEMENT OF CLUSTER HEADACHE IS PHARMACOTHERAPY IN PATIENTS WITH RESISTANT CLUSTER HEADACHE REGARDING PHARMACOTHERAPY INTERVENTIONAL THERAPIES SUCH AS RADIOFREQUENCY OF PTERYGOPALATINE AND OCCIPITAL NERVE STIMULATION ARE MIGHT BE NEEDED